Children, comorbidities and COVID-19 - What tilts the balance? - Shukla, Umesh; Radhakrishnan, Nita; Bhakhri, Bhanu Kiran; Shankar, Ravi; Ghosh, Sohini; Jain, Vikas; Singh, Dharmendra K; Gupta, Devendra K (Asian Journal of Medical Sciences, 2021)
Background: Data on the outcome of children with SARS-COV-2 infection (COVID-19) is still evolving as the pandemic unfolds. Aims and Objective: The present study aims at describing the clinical severity, course and outcome of COVID-19 in children who had underlying illnesses or co-infections. Materials and Methods: Retrospective, single center, observational study, conducted in a pediatric tertiary care center at Noida (National Capital Region, India). Results: We analyzed the data of 15 children with co-morbidities associated with COVID-19. Cancer (n=4, 26.6%), co-infections (n=5, 33.3%), Thalassemia major (n=2, 13.3%) and one child each with celiac disease, cholelithiasis, Duchenne muscular dystrophy and multiple rib fractures were diagnosed with COVID-19. None were asymptomatic. 9 children (60%) had mild symptoms and 4 had moderate symptoms (26.6%) with respiratory distress. 2 children had severe respiratory distress requiring high flow oxygen. Convalescent plasma, IVIG, Oseltamivir, Azithromycin, Hydroxychloroquine were given as treatment in varying combinations. All children recovered from COVID-19. Conclusion: Active malignancy, hypogammaglobinemia, underlying lung disease were associated with moderate to severe symptoms in this series of patients. Convalescent plasma helped in both children with severe hypoxia.